Neighbours vs. strangers discrimination in Water Rail (Rallus aquaticus) - Alexandru Nicolae STERMIN; Alin DAVID; Cătălina DRAGOI; Mirela CÎMPEAN; Karina Paula BATTES (Studia Universitatis Babeș-Bolyai. Biologia, 2017)
Water Rail (Rallus aquaticus) manifest strongly intra- and interspecific aggressivity. In our study we test the Water Rail’s reaction to the calls of conspecifics neighbours and strangers, to conclude if they express the “neighbour-stranger discrimination” (NSD) and / or “the dear enemy effect” (DEE) behaviour as evolutionary attributes that would reduce the energy consumption. Ten points located 100 m apart inside the Sic Reedbeds wetland were selected. In each point the acoustic reactions to spontaneous and playback of territorial Water Rail’s call were counted for three days (18, 19 and 20 April 2011), between 6:00 – 8:00 p.m.. A statistically significant difference was found between the number of songs recorded after spontaneous activity and the number of calls recorded after playback. The results argues the hypothesis that individuals of this species recognize their neighbours and react less aggressively towards them. Moreover, our findings indicated that response to neighbours’ calls follows a constant trajectory during the first or second half of the minute while the reaction towards foreigners is significantly losing intensity during the second half of the minute. The results suggest that the NSD and DEE are expressed in the Water Rail behaviour.